2013
DOI: 10.1088/0953-8984/25/42/426005
|View full text |Cite
|
Sign up to set email alerts
|

DC magnetic susceptibility and neutron powder diffraction analysis of the perovskite-type compounds LaYbO3and LaHoO3

Abstract: Magnetization measurements and neutron powder diffraction analyses followed by Rietveld refinement have been carried out in order to investigate the magnetic structures of LaYbO3 and LaHoO3. Both compounds exhibit a negative thermal expansion along the a and b axes. In LaYbO3 Yb(3+) spins order at 2.4 K according to a FyGz-type structure, belonging to the Pn'ma' magnetic space group. Conversely, LaHoO3 is paramagnetic down to 1.5 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…1), which is consistent with Bharathy's crystallographic data on single crystals of interlanthanides [6]. The unit cell parameters obtained are also consistent with those reported by Martinelli et al [12]. The grain size of all samples is in the micron range as they were calcined at high temperature for a long time.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1), which is consistent with Bharathy's crystallographic data on single crystals of interlanthanides [6]. The unit cell parameters obtained are also consistent with those reported by Martinelli et al [12]. The grain size of all samples is in the micron range as they were calcined at high temperature for a long time.…”
Section: Resultssupporting
confidence: 91%
“…A comprehensive study of preparation and stability of interlanthanide perovskites was done by Berndt et al [2] and their unique magnetic properties were studied by Kentaro et al [7]. Recently, Artini et al presented a comprehensive study of the preparation and structural properties of interlanthanide perovskite compounds [4,5,12]. Bharathy et al [6] reported the growth of single crystals of the interlanthanides series LaLn'O 3 (Ln'=Y, Ho-Lu) using molten hydroxide fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…In LaErO 3 magnetic moments approximately lie in a plane formed by the two axial O(1) atoms and two equatorial O(2) ones, pointing towards the centre of one of the octahedron edges. This arrangement is somehow similar to that detected in LaYbO 3 , despite its different magnetic structure (F y G z -type ordering) [12]: here the ordered magnetic moments lie in the plane formed by the four O(2) atoms, but also in this case the moments point towards the centre of one of the octahedron edges (figure 3).…”
Section: Orthorhombic Laerosupporting
confidence: 77%
“…In this structure the smaller Er 3+ ion is in 6-fold coordination and located at the centre of an octahedron, whereas the larger La 3+ ion displays a 12-fold coordination. The octahedral tilting in LaErO 3 corresponds to the a + b − b − system (N. 10) proposed by Glazer for perovskite structures [24], as in LaYbO 3 and LaHoO 3 [12].…”
Section: Orthorhombic Laeromentioning
confidence: 93%
See 1 more Smart Citation